Influence of the extracorporeal membrane oxygenation system centrifugal pump operation mode on blood damage - M. S. Isaeva; A. I. Petrov; Ye. P. Banin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
One of the key tasks in the development of mechanical circulatory support pump is to take into account its interaction with blood components and their corresponding damage. Within the framework of this study, numerical modeling of the pump operation in different modes is carried out and an assessment of the corresponding change in the values of hemolysis and thrombosis is made. It is found that the most dangerous operating modes also change depending on the parameter under consideration: hemolysis demonstrated the greatest dependence on rotation rate, thrombosis — on flow rate. It is also noted that regardless of the damage parameter taken into account, the greatest contribution to blood damage is made by volute, but the balance between the contribution of the pump elements vary depending on the damage parameter under consideration. The obtained results demonstrate that in order to create a safe mechanical circulatory support pump, during its design and optimization process it is necessary to take into account both hemolysis and thrombosis, as well as the dynamics of system operation.